DISTRIBUSI UKURAN IKAN HASIL TANGKAPAN PURSE SEINE KM. BINTANG SAMPURNA-B DI WPP 572 DAN 573 - Aditya Bramana; Liya Tri Khikmawati; Noar Muda Satyawan; Ario Anggara Mukti (Fakultas Perikanan dan Ilmu Kelautan, 2020)
The fisheries sector has a strategic role in national development. WPP 572 and 573 are the broad waters and located in the Indian ocean. This area has a quiet fish potential, especially from group of pelagic fishes as skipjack tuna, bigeye tuna, mackerel scad, yellowfin tuna, Indian mackerel, and mackerel tuna. However, in terms of utilization of fish resources, WPP 572 and 573 are currently experiencing a fully exploited period, especially for small and large pelagic fish. One of the methods to overcome fully exploited conditions is by managing the limitation on the size of fish that are fit to be caught. The method used in this research was a descriptive method. The sample was taken based on the purposive sampling method, by taking several types of fish caught according to their respective types which were considered to represent all the fish that had been caught. The number of fish samples adjusts to the capacity of the large pan which contains 18-20 large fish, and 50-100 small fish. The total number of catches was 75,878 kg. The main catch was 57,435 kg and bycatch was 18,443 kg. Percentage of catches were skipjack tuna (72% feasible, 28% unfit), baby tuna (100% unfit), yellowfin tuna (51% feasible, 49% unfit), mackerel scad, mackerel tuns, dolphinfish, and other fish (100% feasible). The whole fish caught in KM Bintang Sampurna-B according to the number of samples measured shows that 74% are fit to catch and 26% are not fit to be caught.